Implementation of K-Means and K-Medians Clustering in Several Countries Based on Global Innovation Index (GII) 2018 - Famalika, Ade; Sihombing, Pardomuan Robinson (Universitas PGRI Semarang, 2021)
The Global Innovation Index (GII) is an instrument to assess the ranking of innovation capabilities of all countries. The sub-index of the GII has seven enabler pillars: Institutions, Human Capital and Research, Infrastructure, Market sophistication, Business Sophistication, Knowledge and Technology Outputs, and Creative Outputs. The k-means method and k-medians method are methods for cluster countries based on GII. Cluster 1 in k-means method consists of 48 Countries, Cluster 2 consists of 45 Countries and Cluster 3 consists of 33 Countries and has the average value of seven variables are the highest. Cluster 1 in k-medians method consists of 33 Countries and has the average value of seven variables are the highest., Cluster 2 consists of 53 Countries and Cluster 3 consists of 40 Countries. The result clustering with using k-means method and k-medians method showed that k-medians is better than k-means method because the variance value of k-medians is smaller than k-means.Â